1992
DOI: 10.1242/dev.115.4.1087
|View full text |Cite
|
Sign up to set email alerts
|

MHox: a mesodermally restricted homeodomain protein that binds an essential site in the muscle creatine kinase enhancer

Abstract: Myogenic helix-loop-helix (HLH) proteins, such as myogenin and MyoD, can activate muscle-specific transcription when introduced into a variety of nonmuscle cell types. Whereas cells of mesodermal origin are especially permissive to the actions of these myogenic regulators, many other cell types are refractory to myogenic conversion by them. Here we describe a novel homeodomain protein, MHox, that binds an A+T-rich element in the muscle creatine kinase (MCK) enhancer that is essential for muscle-specific transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…To achieve this, we crossed Foxf2 f/f mice with Prx1 -Cre mice to generate Foxf2 osp −/− mice. Prx1 is expressed in mesenchymal osteoblast progenitors in limb buds and the craniofacial mesenchyme 27 . Prx1 + cells have also been reported as mesenchymal osteoblast progenitors residing in both the periosteum of cortical bone and the bone marrow in adult mice 28 30 .…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this, we crossed Foxf2 f/f mice with Prx1 -Cre mice to generate Foxf2 osp −/− mice. Prx1 is expressed in mesenchymal osteoblast progenitors in limb buds and the craniofacial mesenchyme 27 . Prx1 + cells have also been reported as mesenchymal osteoblast progenitors residing in both the periosteum of cortical bone and the bone marrow in adult mice 28 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Some links between the MyoD family and other transcription factors have been suggested. For example, exogenous expression of myogenin induces MEF2 binding activity (19,93), an intact A/T-rich site in the MCK enhancer is required for transactivation of a reporter gene by myogenic HLH proteins (18), and myosin heavy-chain IIB regions that contain MEFi and A/T-rich sites synergistically increase reporter expression when placed together upstream of a basal promoter (78). Since MyoD family members are not expressed in the heart at any time during development (3,44,65,74), the role of E boxes and their putative binding factors in cardiac gene regulation is yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6). Others have shown that an MCK enhancer A/T-rich mutation decreases enhancer activity in skeletal myocytes and prevents transactivation by HLH myogenic regulators in nonmuscle cells (18). A cloned novel homeodomain protein, MHox, that binds this site in vitro is expressed in mesodermal tissues of the mouse embryo and at high levels in adult mouse skeletal muscle, heart, and uterus (18).…”
Section: Sc)mentioning
confidence: 99%
“…Similarly, Osterix (Osx) + cells reside in bone marrow stroma during fetal development, and further form perivascular, osteogenic, and adipogenic cells [ 25 , 34 ]. Prx1 is highly expressed by limb bud mesenchymal progenitors during long bone development [ 35 ], and genetic lineage tracing by Prx1-Cre labels all skeletal lineage cells in long bones, including skeletal stem/progenitor cells (SSPCs), osteoblasts, osteocytes, chondrocytes, and adipocytes [ 36 ].…”
Section: Functional Heterogeneity Of Bmsc Subpopulations In Physiolog...mentioning
confidence: 99%